Targeting c‐MET by LY2801653 for treatment of cholangiocarcinoma. Issue 12 (12th January 2016) - Barat, Samarpita; Bozko, Przemyslaw; Chen, Xi; Scholta, Tim; Hanert, Franziska; Götze, Julian; Malek, Nisar P.; Wilkens, Ludwig; Plentz, Ruben R.
Abstract : Palliative treatment options for human cholangiocarcinoma (CCC) are quite limited and new therapeutic strategies are of utmost need. c‐MET has been shown to be deregulated in many cancers, but the role of c‐MET in the carcinogenesis of CCC remains unclear. The main purpose of this study is to evaluate the expression and also to investigate the role of c‐MET and its effective inhibition for the treatment of CCC. In this study we investigated the effects of LY2801653, a small‐molecule inhibitor with potent activity against MET kinase, in human CCC cell lines and in vivo using a xenograft mouse model. We have investigated the role of c‐MET and its inhibitory effects on migration, invasion, colony formation, MET downstream targets, and CCC tumor growth. We also analyzed the role of apoptosis and senescence as well as the influence of hypoxia in this context. c‐ MET and p‐MET were expressed in 72% and 12.5% of human CCC tissues and in TFK‐1, SZ‐1 cell lines. MET inhibition was achieved by blocking phosphorylation of MET with LY2801653 and subsequent down regulation of c‐MET downstream targets. Treatment showed in a xenograft model potent anti‐tumor activity. LY2801653 is an effective inhibitor and suppress the proliferation of CCC cells as well as the growth of xenograft tumors. Therefore, inhibition of c‐MET could be a possible alternative approach for the treatment of human CCC. © 2016 Wiley Periodicals, Inc.